Attention to the Details: How Variations in U.S. Grass-Fed Cattle-Feed Supplementation and Finishing Date Influence Human Health - Krusinski, Lucas; Sergin, Selin; Jambunathan, Vijayashree; Rowntree, Jason E.; Fenton, Jenifer I. (Frontiers in Sustainable Food Systems, 2022)
As the global population increases, so does meat consumption. This trend is accompanied by concerns regarding the meat industry, and consumers are demanding transparency on the environmental and health effects of the products they are purchasing. Many leading health organizations recommend reducing red meat consumption. Nevertheless, no differentiation is made among red meats and beef. The beef production system is generally ignored despite nutritional differences between grain- and grass-fed beef. Compared to grain-fed beef, grass-fed beef contains a healthier fatty acid profile, including more omega-3 polyunsaturated fatty acids and conjugated linoleic acid, and increased concentrations of phytochemicals desired by health-conscious customers. However, there is a lack of consistency among grass-fed beef in the United States regarding clear product labeling and cattle dietary components. Grass-fed beef labeling confusion has emerged, including misunderstandings between grass-fed and grass-finished beef. Along with this, previous studies observed significant nutritional variation among grass-finished beef from different producers across the country. Cattle diet has the strongest influence on the nutritional composition of beef. Therefore, understanding differences in feeding practices is key to understanding differing nutritional quality of grass-fed beef. Feeding cattle diverse pastures composed of multiple plant species including grasses and legumes managed in a rotational grazing fashion results in higher omega-3 polyunsaturated fatty acids and phytochemical levels in beef compared to feedlots and monocultures. Seasonal differences including changes in temperature, rainfall, grazing practices, and plant growth cycles affect the nutritional composition of feeds and ultimately meat. Additional feeds utilized in grass-fed beef production systems such as conserved forages may reduce or increase health-promoting nutrients in grass-fed beef, while supplements such as grape byproducts and flaxseed may improve its nutritional profile. Further research should measure the effects of individual feedstuff and the finishing period on the nutritional profile on grass-fed beef. A better understanding of these details will be a step toward the standardization of pasture-raised ruminant products, strengthening the relationship between grass-fed beef consumption and human health.